Psychological distress and dyslipidemia in adult women: A 6-years follow up study in Bogor City, Indonesia - Sulistyowati Tuminah Darjoko; Sudarto Ronoatmodjo; Srilaning Driyah; Dewi Kristanti; Dwi Hapsari Tjandrarini (Faculty of Medicine, Universitas Trisakti, 2022)
BACKGROUNDDyslipidemia is of global occurrence, with a prevalence 30% or higher in several countries, including Indonesia. One risk factor of dyslipidemia is physical or mental stress, that is more frequent in women. This study aimed at investigating the association between psychological distress and dyslipidemia in adult women. METHODSThis observational longitudinal study involved 1850 women aged 25 years and older at baseline. Dyslipidemia was determined from the ratio of low- density lipoprotein to high-density lipoprotein. Psychological distress was determined using the 20-item self-reporting questionnaire. Data analysis was by Cox regression for calculating the hazard ratio of the incidence of dyslipidemia as predicted by the psychological distress. RESULTSAmong the 1474 participants without dyslipidemia at baseline, 545 (36.9%) developed dyslipidemia during 6 years of monitoring, while 93 (6.3%) had a history of psychological distress. There was a significant association between psychological distress and dyslipidemia (HR = 3.08; 95% CI: 2.33- 4.07). Cox regression revealed that the association was still found to be significant after a further adjustment for the variables of age, BMI, menopause, smoking status, physical activity, and carbohydrate and fat intakes (HR=2.8; 95% CI: 2.10 - 3.77). CONCLUSIONSDyslipidemia incidence was high among adult women in Bogor. Women with psychological distress had higher incidence rates of dyslipidemia than women without psychological distress. Psychological distress in women was statistically significantly associated with incidence rate of dyslipidemia. This finding highlights the importance of the need for a dyslipidemia- reduction program in women through prevention and control of psychological distress.